Activity of Matrix Metalloproteinase 2 and 9 in Follicular Fluid and Seminal Plasma and Its Relation to Embryo Quality and Fertilization Rate - M Atabakhsh; I Khodadadi; I Amiri; H Mahjub; H Tavilani (JRI, 2018)
Background: The purpose of this study was to evaluate the activity of matrix metalloproteinase 2 (MMP-2) and 9 (MMP-9) in follicular fluid and seminal plasma and the correlation of their activities with parameters that are important in successful intracytoplasmic sperm injection (ICSI). Methods: Seventy-four infertile couples admitted to the Research Center for Endometrium and Endometriosis to carry out ICSI method were enrolled in this study. Follicular fluid was collected after retrieving the oocyte. In addition, semen samples were collected and seminal plasma was used for determination of MMP2 and MMP-9 activity. Gelatin zymography electrophoresis was applied to measure MMPs activities in follicular fluid and seminal plasma. Results: In follicular fluid, there was a positive correlation between MMP-2 activity with oocyte (r=0.27, p=0.021) or embryo quality (r=0.30, p=0.014), but no correlation was observed between MMP-2 activity and oocyte count or fertilization. Activity of MMP-9 showed positive correlation with oocyte morphology (r=0.29, p=0.014). In addition, MMP-2 activity of seminal plasma had positive correlation with sperm count (r=0.28, p=0.015), fertilization (r=0.28, p=0.02), and embryo quality (r=0.28, r=0.026). Conclusion: MMP2 and MMP9 activities in seminal plasma have a positive effect on sperm count and motility. MMP-2 and MMP-9 activity in follicular fluid and seminal plasma could be important factors in embryo quality in patients undergoing ICSI and may affect the outcome of ICSI.